Studi Keprimaan dalam Modul: Submodul Prima, Prima Lemah, Hampir Prima, dan n- Hampir Prima - Ambar, Jinan; Afdhaluzzikri, Muhammad (Program Studi Matematika, 2024)
Module theory, as a branch of abstract algebra, is a field of study that extends the concept of vector spaces into a more general framework, finding broad applications across various mathematical fields. The concept of prime numbers, initially abstracted by Dedekind in the form of prime ideals, underwent further development by mathematicians. Anderson generalized it into weak prime ideals, while Sharma developed the concept of nearly prime ideals. After Noether introduced the concept of modules, Dauns brought this primality notion into module theory under the name of prime submodules. Subsequently, Khashan generalized it into weak and nearly prime submodules. The latest development came from Azizi, who introduced the concept of nearly prime submodules into n-nearly prime submodules. In this context, this article discusses several key characteristics of prime submodules and their generalizations, providing a deep understanding of their fundamental structures and properties. Through this understanding, we can explore various applications of module theory in various mathematical contexts and delve into the complexities inherent in the study of primality and submodule structures within modules. The purpose of this research is to explain some structures and properties of prime submodules. This research uses the literature review method, which is by collecting information from various reading sources related to prime submodules and their generality. The result of this research is an explanation of some structures and properties of prime submodules and their examples.